Adoption and impacts of microirrigation technologies: empirical results from selected localities of Maharashtra and Gujarat states of India - Namara, Regassa E.; Upadhyay, Bhawana; Nagar, R.K. (International Water Management Institute, 2005)
This report analyzes the economics of alternative microirrigation technologies ranging from low-cost drip and sprinkler systems to the capital-intensive systems, the determinants of adoption of microirrigation technology, the poverty outreach of the different microirrigation systems, and the sustainability implications of microirrigation adoption.